Writing errors of EFL undergraduate students in the online writing course - Kiatkheeree, Parussaya (International Journal of English Language and Pedagogy, 2024)
Writing is considered the most difficult skill for learners especially for those who learn English as a foreign language. This study aims to explore the sources of errors occurred in the writing of EFL undergraduate students in the online environment. The data were collected from 10 essays for final examination composed by 10 Thai students studying in English major in one Thai university. The essays were coded and classified into different categories and themes. The findings revealed that errors made by Thai students came from their less effectiveness in the use of language. Their errors included not only word choice, verb tense, preposition, pronoun, but also their lack understanding of writing process. In addition, their writing skills and accuracy of language forms did not meet the criteria as expected. This study provides implications for EFL teaching staff at the university level in which they should promote more writing practice and pay more attention to writing errors of students in any online courses.